Pembelajaran Budaya Alam Minangkabau (BAM) sebagai Wadah Pelestarian Kearifan Lokal: antara Harapan dan Kenyataan - Agustina . (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2012)
The wise proper efforts to preserve the local wisdom of Minangkabau culture in West Sumatra are through offering the Minangkabau natural culture as a local content subject in schools. This subject has been taught for almost twenty years. However, the results of teaching this subject do not meet the expectation. To make this subject as a way to preserve the local wisdom, the stake holders should have the strong commitment in improving the teaching and learning process through providing the learning equipments that are relevant with the advance of technology, preparing professional teachers, proving good examples from both parents and society, and teaching and using Minangkabau language as the learning materials and the medium of istruction in the process of teaching and learning Keywords: Minangkabau Culture, Local Wisdom. Preservation, Learning